Practical application of mathematical calculations and statistical methods for the routine haematology laboratory. (8th September 2022) - Padmore, Ruth; Petersen, Katryna; Campbell, Chris; Chennette, Manon; Sabourin, Ann; Shaw, Julie
Abstract: Background: Statistical analyses are embedded as critical functions in the routine haematology laboratory. Aim: This educational article is aimed at providing an overview of these topics and practical application examples. Materials, Methods, and Results: Topics covered include mathematical conversion between units, maintaining a quality control (QC) system, statistical methods for reagent validation, and determining uncertainty of measurement (UoM). Discussion: Additional considerations may be required when a regional laboratory program is in place, such as the harmonization of INR results and determination of therapeutic reference intervals for unfractionated heparin therapy. Conclusion: The coauthors of this manuscript are fortunate to be part of regional network of hospital laboratories, the Eastern Ontario Regional Laboratory Association (EORLA).